Preparation method of transition-metal-doped bimetallic MOF-derived heterostructure, obtained product and application
By preparing the transition metal-doped bimetallic MOF-derived Co3S4-MoS2 heterostructure, the problem of insufficient adsorption and catalytic conversion of polysulfides in lithium-sulfur batteries is solved, and the capacity and cycle stability of lithium-sulfur batteries are improved.
Patent Information
- Application Number
- CN202411996527.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The practical application of lithium-sulfur batteries is hindered by the intrinsic insulation, the shuttle effect of polysulfide intermediates and the slow reaction kinetics, resulting in poor electrochemical kinetics of sulfur.
By preparing transition metal-doped bimetallic MOF-derived heterostructures, using bimetallic MOF as a template, doping transition metal elements to increase active sites, and forming Co3S4-MoS2 heterostructures through solvothermal reactions, as an electrocatalyst for the battery separator to adsorb polysulfides and accelerate the redox reaction kinetics of sulfur.
This heterostructure can effectively adsorb polysulfides, inhibit the shuttle effect, accelerate the redox reaction kinetics of sulfur, thereby improving the capacity and cycle stability of lithium-sulfur batteries.
Smart Images

Figure CN119797443A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a transition metal-doped bimetallic MOF-derived heterostructure, a obtained product and an application thereof, and belongs to the technical field of battery materials. Background Art
[0002] With the continuous development of portable electronic devices and electronic vehicles, lithium-ion batteries are difficult to meet the growing energy storage needs due to their limited theoretical capacity and high cost. Therefore, the search for lithium secondary batteries with good cycle performance, high energy density and low cost has become a research hotspot. Among them, lithium-sulfur (Li-S) batteries have a high theoretical specific capacity (1675mAhg -1 ), abundant sulfur resources and environmental friendliness. However, the practical application of lithium-sulfur batteries is still hindered by several challenges: (1) the intrinsic insulation of S and Li2S; (2) the "shuttle effect" of polysulfide intermediates (soluble polysulfides migrate from the cathode to the anode, reducing sulfur utilization and corroding lithium metal); (3) the slow reaction kinetics between polysulfides (LiPSs) and Li2S, resulting in poor electrochemical kinetics of sulfur in lithium-sulfur batteries.
[0003] As one of the important components of lithium-sulfur batteries, the separator mainly acts as an electronic insulator to prevent internal short circuits. Commercial separators are usually polymer membranes (PP, PE, etc.) containing a large number of micropores, and their pore size is much larger than that of polysulfides. Therefore, soluble polysulfides can easily shuttle freely through the micropores of the separator, resulting in problems such as battery capacity loss. Therefore, it is necessary to modify the separator of lithium-sulfur batteries so that it can effectively adsorb lithium polysulfide and reduce the activation energy of the reaction, so as to inhibit the shuttle effect and accelerate the reaction kinetics, thereby improving the capacity and cycle stability of lithium-sulfur batteries. Metal sulfides are considered to be potential catalysts for lithium-sulfur batteries due to their polarity and certain catalytic ability. However, due to the inherent weak conductivity of sulfides and the single adsorption catalytic function, they cannot simultaneously meet the requirements of rapid transfer of electrons and ions, strong adsorption of polysulfides, and rapid redox reaction kinetics, so that 70% of the sulfur active substances cannot be completely converted. Based on this, in order to accelerate the redox kinetics of polysulfides, heterostructure engineering has been explored by many researchers as a feasible strategy for Li-S batteries. Reference (Chemical Engineering Journal 441(2022)136006) designed Co3S4 hollow polyhedrons decorated with MoS2 nanosheets (Co3S4-MoS2) and applied them to the adsorption of tetracycline (TC) in aqueous solution. Reference (Applied Catalysis B:Environmental 264(2020)118514) used a dual template method to prepare MoS2@Co3S4 (MoS2@Co3S4 / NFA) supported on nanofiber aerogel for photocatalysis. Reference (Chemical Engineering Journal 475(2023)146324) designed and prepared Co3S4 / MoS2 heterostructures and fixed them on N-doped porous carbon (NPC) to explore their peroxidase-like activity. The literature (Applied Materials Today 26 (2022) 101311) synthesized the Co3S4-MoS2 heterostructure using the precursor solubility control method and applied it to the HER catalytic reaction, proving that there is electron transfer between the heterogeneous interfaces, which improves the electron migration rate during the reaction. However, the study found that the Co3S4-MoS2 heterostructure has problems with insufficient polysulfide adsorption and catalytic conversion when used in battery separators. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a transition metal-doped bimetallic MOF-derived heterostructure and the obtained transition metal-doped bimetallic MOF-derived heterostructure. The heterostructure is prepared using a bimetallic MOF as a template, and the number of active sites is increased by doping transition metal elements, the electronic structure of Co is adjusted, the construction of the heterostructure accelerates the transfer of electrons, and the synergistic effect between the two-component sulfides enables the heterostructure to effectively adsorb polysulfides when used as a battery separator electrocatalyst, and accelerates the redox reaction kinetics of sulfur, inhibits the "shuttle effect" of polysulfides, thereby improving the capacity and cycle stability of lithium-sulfur batteries.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a transition metal-doped bimetallic MOF-derived heterostructure, the method comprising the following steps:
[0007] (1) Co salt, transition metal M salt, dimethyl imidazole and methanol are uniformly mixed, and then allowed to stand to allow metal ions to combine with organic ligands to obtain a bimetallic MOF precursor;
[0008] (2) dispersing the bimetallic MOF precursor in ethanol to obtain solution 1; dissolving sodium molybdate and thioacetamide in water to obtain solution 2; stirring and mixing solution 1 and solution 2, heating them to perform a solvothermal reaction, and collecting the product after the reaction;
[0009] (3) The product is calcined under an inert atmosphere to obtain a transition metal-doped bimetallic MOF-derived heterostructure.
[0010] Furthermore, in step (1), the transition metal M can be selected from one of transition metals such as Fe, Ni, Zn, Cu, Mn, etc., preferably Zn. The salt of the transition metal M is a soluble salt of the transition metal, such as a chloride or nitrate of the transition metal, preferably a nitrate of the transition metal.
[0011] Furthermore, in step (1), the Co salt is a soluble salt of cobalt, such as chloride or nitrate.
[0012] Furthermore, in step (1), the molar amount of Co is 70-90% of the total molar amount of Co and the transition metal M, such as 70%, 80%, 90%, preferably 90%.
[0013] Preferably, in step (1), the transition metal M is Zn, the sum of the molar numbers of Co and Zn is 3 mmol, and the molar ratio of Co to Zn is 9:1.
[0014] Furthermore, in step (1), dimethylimidazole is used as an organic ligand, and its main function is to act as a connector of metal ions. Dimethylimidazole connects Co and transition metal M ions to form a periodic network porous structure. The ratio of the total molar amount of Co salt and transition metal M salt to the molar amount of dimethylimidazole is 1:6-10, for example, 1:6, 1:7, 1:8, 1:9, 1:10, preferably 1:8.
[0015] Furthermore, in step (1), methanol is used as a solvent. The solvent has two functions: one is to provide a reaction medium and mix the components evenly; the other is to act as a structure-directing agent. Methanol enhances the deprotonation ability of the solution and ultimately forms a regular rhombic dodecahedron structure.
[0016] Furthermore, in step (1), the concentrations of Co salt, transition metal M salt, and dimethylimidazole in the solvent can control the particle size of the rhombic dodecahedron, and the total concentration of Co salt and transition metal M salt in methanol is 0.01-0.06 mol / L, for example, 0.015 mol / L, 0.02 mol / L, 0.03 mol / L, 0.06 mol / L, preferably 0.06 mol / L.
[0017] Furthermore, in step (1), there is no particular requirement for the order in which the Co salt, the transition metal M salt, the dimethylimidazole and the solvent are mixed. After mixing, the mixture is stirred at room temperature for 20-40 min, for example, 20 min, 30 min, and 40 min, at a stirring speed of 200-400 r·min -1 , for example 200 r / min -1 、300r·min -1 、400r·min -1 After stirring, the solution is allowed to stand at room temperature for 12-24 hours, for example, 12 hours, 15 hours, 18 hours, 20 hours, 24 hours.
[0018] Further, in step (1), after standing, the sample is centrifuged, washed, and dried to obtain a bimetallic MOF precursor. The washing is performed with methanol, and the drying temperature is 60-80° C., for example, 60° C., 70° C., 80° C., preferably 70° C. The drying time is generally 9-13 hours, for example, 9h, 10h, 11h, 12h, 13h, preferably 12h.
[0019] Furthermore, in step (2), the mass ratio of the bimetallic MOF precursor to thioacetamide is 7-10:12, for example, 7:12, 8:12, 9:12, 10:12, preferably 8:12.
[0020] Furthermore, in step (2), sodium molybdate may be anhydrous sodium molybdate or dihydrate sodium molybdate, and the molar ratio of sodium molybdate to thioacetamide is 1-3:8, for example, 1:8, 1.5:8, 2:8, 2.5:8, 3:8, preferably 2.5:8.
[0021] Further, in step (2), the bimetallic MOF can be dispersed in ethanol by at least one of stirring, ultrasound, etc., and the dispersion time is 10-30 minutes, for example, 10 minutes, 20 minutes, 30 minutes. Ethanol is a solvent, and the role of the solvent is to provide a medium for the reaction. The bimetallic MOF precursor can be decomposed in ethanol, which is beneficial to the subsequent reaction. Ethanol is a solvent, and its amount can be selected according to actual needs. Thioacetamide and sodium molybdate are soluble in water, and water is a solvent, and its amount can be selected according to actual needs.
[0022] Furthermore, in step (2), after solution 1 and solution 2 are mixed, they are stirred at room temperature for 20-40 min, for example, 20 min, 30 min, 40 min, and the stirring speed is 200-400 r·min -1 , for example 200 r / min -1 、300r·min -1 、400r·min -1 .
[0023] Further, in step (2), the solvent thermal reaction is carried out in a reactor and is divided into two stages. The first stage is the process of forming (MCo)3S4, the solvent thermal reaction temperature is 110-140°C, for example, 110°C, 120°C, 130°C, 140°C, and the reaction time is generally 3-5 hours, for example, 3 hours, 4 hours, 5 hours. Preferably, the reaction temperature is 120°C and the reaction time is 4h. The second stage is the process of forming MoS2, the solvent thermal reaction temperature is 180-220°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, and the reaction time is generally 15-18h, for example, 15h, 16h, 17h, 18h, and the preferred reaction temperature is 180°C and the reaction time is 16h.
[0024] Further, in step (2), after the solvothermal reaction is completed, the sample is centrifuged, washed, and dried to obtain a transition metal-doped bimetallic MOF-derived disulfide heterostructure. The washing is performed using ethanol, and the drying temperature is 60-80° C., for example, 60° C., 70° C., 80° C., preferably 70° C. The drying time is generally 9-13 hours, for example, 9h, 10h, 11h, 12h, 13h, preferably 12h.
[0025] Furthermore, in step (3), the product of step (2) is calcined under an inert gas to remove impurities in the sample and improve the crystallinity of the product. The inert gas can be nitrogen, argon, etc. The calcination temperature is 320-360°C, such as 320°C, 330°C, 340°C, 350°C, 360°C, preferably 350°C, and the calcination time is 2-2.5h.
[0026] The transition metal-doped bimetallic MOF-derived heterostructure prepared according to the method of the present invention is a 3D structure, in which the transition metal element is uniformly doped, the electronic structure of Co is adjusted, the construction of the heterostructure accelerates the transfer of electrons, and the synergistic effect between the two-component sulfides enables the heterostructure to effectively adsorb polysulfides when used as an electrocatalyst for battery separators, and accelerates the redox reaction kinetics of sulfur, inhibiting the "shuttle effect" of polysulfides. Therefore, the present invention also provides a transition metal-doped bimetallic MOF-derived heterostructure prepared according to the above method and the use of the heterostructure as a battery separator electrocatalyst.
[0027] The present invention also provides a modified battery separator, which includes a battery separator body, on which an electrocatalyst layer is coated, wherein the electrocatalyst layer contains the transition metal-doped bimetallic MOF-derived heterostructure of the present invention. The transition metal-doped bimetallic MOF-derived heterostructure coated in the battery separator can inhibit the shuttle effect of polysulfides and improve the capacity and cycle stability of the battery.
[0028] Furthermore, the electrocatalyst layer is coated on the upper surface or the lower surface of the battery separator body. The battery separator body is a polymer separator commonly used in existing batteries, such as a polypropylene (PP) separator or a PE separator with micropores.
[0029] Furthermore, the thickness of the electrocatalyst layer is 8-12 μm.
[0030] Further, the electrocatalyst layer is composed of a transition metal-doped bimetallic MOF-derived heterostructure and a binder, and the mass ratio of the transition metal-doped bimetallic MOF-derived heterostructure to the binder is preferably 9: 1. The binder can be a special binder for lithium-sulfur batteries, such as LA133, polytetrafluoroethylene, and the like.
[0031] Furthermore, the preparation method of the modified battery separator is: the transition metal-doped bimetallic MOF-derived heterostructure and the binder are uniformly stirred in proportion to form a slurry, the slurry is applied to the surface of the battery separator body, and the modified battery separator is obtained after drying.
[0032] The present invention also provides the use of the above transition metal-doped bimetallic MOF-derived heterostructure or modified battery separator in a lithium-sulfur battery.
[0033] In a specific embodiment of the present invention, a method for assembling a lithium-sulfur battery is also provided, which specifically comprises the following steps:
[0034] (1) grinding sulfur powder and BP2000 carbon black in a mass percentage ratio of 70%:30% for 30 to 40 minutes, and then placing in an oven at 155° C. for 12 hours to obtain a sulfur-carbon positive electrode material;
[0035] (2) The sulfur-carbon cathode material, conductive carbon, and LA133 binder were mixed and ground evenly in a mass ratio of 7:2:1, and the slurry was coated on the surface of the carbon-coated aluminum foil. After vacuum drying at 60°C, the slurry was cut into discs with a diameter of 8 mm to obtain sulfur-carbon electrodes;
[0036] (3) Assemble a button cell in an argon-filled glove box, wherein the positive electrode is a sulfur-carbon electrode, the negative electrode is metallic lithium, the diaphragm is a battery diaphragm modified with a heterostructure electrocatalyst derived from a transition metal-doped bimetallic MOF of the present invention, and the electrolyte is composed of: 1 mol / L lithium bis(trifluoromethylsulfonyl)imide, 1-2 wt % lithium nitrate, and the solvent is a mixture of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. The transition metal-doped bimetallic MOF-derived disulfide heterostructure of the present invention is prepared using bimetallic MOF as a template, wherein each element is doped uniformly, the electronic structure of Co is adjusted, the construction of the heterostructure accelerates the transfer of electrons, and the synergistic effect between the two-component sulfides enables the heterostructure to effectively adsorb polysulfides as a modified battery diaphragm electrocatalyst, accelerate the redox reaction kinetics of sulfur, and inhibit the "shuttle effect" of polysulfides.
[0039] 2. The preparation method of the present invention is simple, the selected active components are all transition metal elements, the required raw materials are widely available, and the production cost is greatly reduced. The obtained heterogeneous structure has a stable structure and excellent catalytic performance.
[0040] 3. The battery separator modified by the disulfide heterostructure derived from the transition metal-doped bimetallic MOF obtained by the present invention has excellent mechanical properties and stability, and no powder shedding occurs after bending and folding. The modified battery separator is used in lithium-sulfur batteries, and the assembled lithium-sulfur batteries have high discharge specific capacity (1455.5mAh / g, 0.2C) and excellent cycle stability, and have broad application prospects in lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1This is the X-ray diffraction (XRD) pattern of the transition metal-doped bimetallic MOF-derived heterostructure electrocatalyst (CoZn)3S4-MoS2 prepared in Example 1.
[0042] Figure 2 Scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) images of the transition metal-doped bimetallic MOF-derived heterostructure electrocatalyst (CoZn)3S4-MoS2 prepared in Example 1.
[0043] Figure 3 This is a photograph of the folding and bending test of the battery separator (CoZn)3S4-MoS2 / PP modified with the transition metal-doped bimetallic MOF-derived heterostructure electrocatalyst prepared in Example 1.
[0044] Figure 4 The discharge specific capacity of the lithium-sulfur battery using the battery separator modified with the (CoZn)3S4-MoS2 electrocatalyst of Example 1 at different current densities. DETAILED DESCRIPTION
[0045] The present invention is further described below through specific examples, but it should be understood that the following description is only exemplary and does not limit the protection scope of the present invention.
[0046] Example 1
[0047] A Zn-doped CoZn-MOFs-derived heterostructure electrocatalyst is prepared, the method comprising:
[0048] 1. Dissolve 0.786 g (2.7 mmol) of Co(NO3)2·6H2O and 0.089 g (0.3 mmol) of Zn(NO3)2·6H2O in 30 mL of methanol to form a uniform solution, then pour it into 20 mL of methanol containing 1.97 g (24 mmol) of dimethylimidazole and heat at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain CoZn-MOFs.
[0049] 2. Disperse 80 mg of CoZn-MOFs in 20 mL of ethanol and ultrasonicate for 20 min. At the same time, add 0.12 g (1.6 mmol) of thioacetamide and 0.121 g (0.5 mmol) of Na2MoO4·2H2O to 20 mL of water, fully dissolve them, and add them to the above CoZn-MOFs ethanol solution. -1After stirring for 20 min, pour into a 100 mL reactor, first react at 120°C for 4 h, then heat to 200°C for 16 h. After cooling, the reactor is centrifuged, the product is washed with ethanol several times, and then dried in a 60°C oven for 12 h.
[0050] 3. The product was calcined at 350 °C under N2 for 2 h to obtain a transition metal-doped bimetallic MOF-derived disulfide heterostructure electrocatalyst (CoZn)3S4-MoS2.
[0051] like Figure 1 As shown in Figure 2, X-ray diffraction (XRD) was used to characterize the heterogeneous structure electrocatalyst. Figure 1 As can be seen in the figure, the heterostructure can see obvious diffraction peaks, corresponding to Co3S4 (PDF#42-1448) and MoS2 (PDF#37-1492). In addition, the synthesized (CoZn)3S4-MoS2 has no diffraction peaks of other impurity phases, which means that the specified sample was synthesized.
[0052] from Figure 2 It can be seen that the morphology of the heterostructure (CoZn)3S4-MoS2 is a hollow dodecahedron. Such a structure has a large specific surface area, which is conducive to exposing more active sites and promoting the adsorption and catalytic conversion of polysulfides. Further, it can be seen from EDS that each element is evenly distributed.
[0053] Example 2
[0054] The transition metal-doped bimetallic MOF-derived electrocatalyst (CoZn)3S4-MoS2 was prepared according to the method of Example 1, except that in step 2, the amount of Na2MoO4·2H2O used was 72.6 mg (0.3 mmol).
[0055] Example 3
[0056] The transition metal-doped bimetallic MOF-derived electrocatalyst (CoZn)3S4-MoS2 was prepared according to the method of Example 1, except that in step 1, the amount of Co(NO3)2·6H2O was adjusted to 0.698 g (2.4 mmol), and the amount of Zn(NO3)2·6H2O was adjusted to 0.178 g (0.6 mmol).
[0057] Example 4
[0058] The transition metal-doped bimetallic MOF-derived electrocatalyst (CoZn)3S4-MoS2 was prepared according to the method of Example 1, except that in step 1, the amount of Co(NO3)2·6H2O was adjusted to 0.611 g (2.1 mmol), and the amount of Zn(NO3)2·6H2O was adjusted to 0.267 g (0.9 mmol).
[0059] Example 5
[0060] The Cu-doped CoCu-MOFs-derived disulfide heterostructure electrocatalyst (CoCu)3S4-MoS2 was prepared according to the method of Example 1, except that: in step 1, 0.698 g (2.4 mmol) of Co(NO3)2·6H2O and 0.113 g (0.6 mmol) of Cu(NO3)2·6H2O were dissolved in 30 mL of methanol to form a uniform solution, which was then poured into 20 mL of methanol containing 1.48 g (18 mmol) of dimethylimidazole and heated at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain CoCu-MOFs.
[0061] Example 6
[0062] The Ni-doped CoNi-MOFs-derived disulfide heterostructure electrocatalyst (CoNi)3S4-MoS2 was prepared according to the method of Example 1, except that: in step 1, 0.786 g (2.7 mmol) of Co(NO3)2·6H2O and 0.088 g (0.3 mmol) of Ni(NO3)2·6H2O were dissolved in 60 mL of methanol to form a uniform solution, which was then poured into 40 mL of methanol containing 1.97 g (24 mmol) of dimethylimidazole and heated at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain CoNi-MOFs.
[0063] Example 7
[0064] The Fe-doped CoFe-MOFs-derived disulfide heterostructure electrocatalyst (CoFe)3S4-MoS2 was prepared according to the method of Example 1, except that: in step 1, 0.089 g (0.3 mmol) of Zn(NO3)2·6H2O was replaced by 0.121 g (0.3 mmol) of Fe(NO3)2·9H2O; in step 2, “first react at 120°C for 4 h, then heat to 200°C for 16 h” was replaced by “first react at 110°C for 5 h, then heat to 180°C for 18 h”.
[0065] Example 8
[0066] The Mn-doped CoMn-MOFs-derived disulfide heterostructure electrocatalyst (CoMn)3S4-MoS2 was prepared according to the method of Example 1, except that in step 1, 0.089 g (0.3 mmol) of Zn(NO3)2·6H2O was replaced by 0.086 g (0.3 mmol) of Mn(NO3)2·6H2O.
[0067] Comparative Example 1
[0068] 1. Same as Example 1.
[0069] 2. Disperse 80 mg of CoZn-MOFs in 20 mL of ethanol and ultrasonicate for 20 min. Then add 20 mL of an aqueous solution containing 0.12 g (1.6 mmol) of thioacetamide to the ethanol solution, stir thoroughly for 20 min, pour it into a 100 mL reactor, and react at 120 ° C for 4 h. After the reactor is cooled, centrifuge the product, wash it with ethanol several times, and then dry it in an oven at 60 ° C for 12 h.
[0070] 3. Disperse 80 mg of the product of step 2 in 20 mL of ethanol and ultrasonicate for 20 min to obtain an ethanol dispersion. At the same time, add 0.12 g (1.6 mmol) of thioacetamide and 0.121 g (0.5 mmol) of Na2MoO4·2H2O to 20 mL of water, fully dissolve them, add them to the ethanol dispersion, and stir at 200 r·min. -1 After stirring for 20 min, pour into a 100 mL reactor and heat to 200°C for 16 h. After cooling, the reactor is centrifuged, the product is washed with ethanol several times, and then dried in a 60°C oven for 12 h.
[0071] 4. The product was calcined at 350 °C for 2 h under N2 to obtain a transition metal-doped bimetallic MOF-derived disulfide heterostructure electrocatalyst (CoZn)3S4-MoS2.
[0072] Comparative Example 2
[0073] 1. Dissolve 0.87 g (3 mmol) of Co(NO3)2·6H2O in 30 mL of methanol to form a uniform solution, then pour it into 20 mL of methanol containing 1.97 g (2.4 mmol) of dimethylimidazole and heat at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain Co-MOFs.
[0074] 2. Disperse 80 mg of Co-MOFs in 20 mL of ethanol and ultrasonicate for 20 min. At the same time, add 0.12 g (1.6 mmol) of thioacetamide and 0.121 g (0.5 mmol) of Na2MoO4·2H2O to 20 mL of water and fully dissolve them. Then add them to the above Co-MOFs ethanol solution and stir at 200 r·min. -1 After stirring for 20 min, pour into a 100 mL reactor, first react at 120°C for 4 h, then heat to 200°C for 16 h. After cooling, the reactor is centrifuged, the product is washed with ethanol several times, and then dried in a 60°C oven for 12 h.
[0075] 3. The product was calcined at 350 °C for 2 h under N2 to obtain the MOF-derived disulfide heterostructure electrocatalyst Co3S4-MoS2.
[0076] Comparative Example 3
[0077] 1. Dissolve 0.786 g (2.7 mmol) of Co(NO3)2·6H2O and 0.089 g (0.3 mmol) of Zn(NO3)2·6H2O in 30 mL of methanol to form a uniform solution, then pour it into 20 mL of methanol containing 1.97 g (24 mmol) of dimethylimidazole and heat at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain CoZn-MOFs.
[0078] 2. Disperse 80 mg of CoZn-MOFs in 20 mL of ethanol and ultrasonicate for 20 min. Then add 20 mL of an aqueous solution containing 0.12 g (1.6 mmol) of thioacetamide to the ethanol solution, stir thoroughly for 20 min, pour it into a 100 mL reactor, and react at 120 ° C for 4 h. After the reactor is cooled, centrifuge the product, wash it with ethanol several times, and then dry it in an oven at 60 ° C for 12 h.
[0079] 3. The product was calcined at 350 °C under N2 for 2 h to obtain the transition metal-doped MOF-derived electrocatalyst (CoZn)3S4.
[0080] Comparative Example 4
[0081] 1. Add 0.12 g (1.6 mmol) of thioacetamide and 0.121 g (0.5 mmol) of Na2MoO4·2H2O to 40 mL of water and heat at 200 r·min. -1 After stirring for 20 min, pour into a 100 mL reactor, first react at 120°C for 4 h, then heat to 200°C for 16 h. After the reactor is cooled, the product is centrifuged, washed with ethanol several times, and then dried in a 60°C oven for 12 h.
[0082] 2. Calcine the product at 350 °C under N2 for 2 h to obtain MoS2.
[0083] Comparative Example 5
[0084] 1. Dissolve 0.87 g (3 mmol) of Co(NO3)2·6H2O in 30 mL of methanol to form a uniform solution, then pour it into 20 mL of methanol containing 1.97 g (2.4 mmol) of dimethylimidazole and heat at a speed of 200 r·min. -1 The mixture was stirred for 30 min and allowed to stand at room temperature for 24 h. The precipitate was centrifuged, washed with methanol and dried in an oven at 60 °C for 12 h to obtain Co-MOFs.
[0085] 2. Disperse 80 mg of Co-MOFs in 20 mL of ethanol and ultrasonicate for 20 min. Then add 20 mL of aqueous solution containing 0.12 g (1.6 mmol) of thioacetamide and 0.148 g (0.5 mmol) of Zn(NO3)2·6H2O to the ethanol solution, stir thoroughly for 20 min, pour it into a 100 mL reactor, and react at 120 ° C for 4 h. After the reactor is cooled, centrifuge the product, wash it with ethanol several times, and then dry it in an oven at 60 ° C for 12 h.
[0086] 3. The product was calcined at 350 °C under N2 for 2 h to obtain the MOF-derived electrocatalyst Co3S4-ZnS.
[0087] Application Example 1
[0088] 80 mg of electrocatalyst and 1.3 ml of LA133 binder were mixed evenly to obtain a coating slurry, and the coating slurry was evenly coated on one surface of a polypropylene separator to obtain a modified battery separator, and the coating layer thickness was about 10 μm. The electrocatalysts were the heterogeneous structure electrocatalysts of Examples 1-8 and the products prepared in Comparative Examples 1-5.
[0089] Verification Example
[0090] 1. Folding and bending test
[0091] The modified battery separator prepared in the application example was subjected to a bending and folding experiment, in which the coated modified battery separator was cut into discs with a diameter of 18 mm using a puncher, and then folded in half twice in succession, and then opened to restore the original shape, and the powder shedding was observed.
[0092] Among them, the photo of the battery separator modified with (CoZn)3S4-MoS2 electrocatalyst in the folding process of Example 1 is as follows Figure 3 As shown, there is no powder shedding phenomenon after bending and folding, indicating that the (CoZn)3S4-MoS2 electrocatalyst modified battery separator prepared in Example 1 has excellent mechanical properties and stability.
[0093] The bending and folding test results of other modified battery separators are shown in Table 1 below:
[0094] Table 1
[0095]
[0096]
[0097] 2. Discharge capacity and rate performance experiment of lithium-sulfur battery
[0098] 2.1 Preparation of carbon-sulfur positive electrode sheet:
[0099] Sulfur powder and BP2000 carbon black were ground at a mass ratio of 7:3 for 30 minutes, and then put into an oven at 155°C for 12 hours to obtain a sulfur-carbon positive electrode material. The sulfur-carbon positive electrode material, conductive carbon, and LA133 binder were mixed and ground evenly at a mass ratio of 7:2:1, and the slurry was coated on the surface of the carbon-coated aluminum foil. After vacuum drying at 60°C, it was cut into discs with a diameter of 8 mm to obtain a sulfur-carbon electrode.
[0100] 2.2 Preparation of lithium-sulfur batteries:
[0101] Assemble 2032 button-type lithium-sulfur batteries. Use sulfur-carbon positive electrode sheets as positive electrodes (8 mm in diameter), lithium sheets (16 mm in diameter) as negative electrodes, and modified battery separators (18 mm in diameter) prepared in the application example as separators. The electrolyte composition is: 1 M molar concentration of lithium bis(trifluoromethylsulfonyl)imide, 2 wt% anhydrous lithium nitrate, wherein the solvent is a mixture of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.
[0102] 2.3 Electrochemical performance test
[0103] The electrochemical performance of different lithium-sulfur batteries was evaluated by constant current charge and discharge tests on the blue electric system (test voltage range was 1.7-2.8V, current density was 0.1C), and the discharge specific capacity of lithium-sulfur batteries was evaluated and compared; the test results are shown in Table 2. It can be seen from Table 2 that the lithium-sulfur battery using the (CoZn)3S4-MoS2 / PP separator of Example 1 has the highest discharge specific capacity, and the first cycle discharge capacity is 1455.7mAh / g at a current density of 0.1C. Compared with the comparative examples, the discharge capacity is greatly improved, indicating that the heterogeneous structure catalyst and element doping have a significant catalytic effect on the redox reaction of sulfur. The discharge specific capacity of the battery of Examples 2-8 is also higher than that of the battery of each comparative example.
[0104] Table 2 Discharge capacity of different batteries at 0.1C (mAh / g)
[0105]
[0106]
[0107] The rate performance was studied by applying different current densities, such as Figure 4 The figure shows the discharge specific capacity of the lithium-sulfur battery using the (CoZn)3S4-MoS2 / PP diaphragm prepared using the product of Example 1 at rates of 0.2C, 0.4C, 0.6C, 1C, and 2C, which are 1405.9mAh / g, 1159.9mAh / g, 1052.6mAh / g, 950.3mAh / g, and 802.7mAh / g, respectively. When the rate returns to 0.4C, the specific capacity can still reach 1109mAh / g, and the specific capacity at 0.4C decreases by only 4%, indicating that the battery using the (CoZn)3S4-MoS2 catalyst-modified diaphragm has good capacity reversibility. The specific discharge capacity of the lithium-sulfur battery obtained by using the modified diaphragms of Examples 2-8 and Comparative Example 1 decreases by 10%-15% from 0.2C through 0.4C, 0.6C, 1C, 2C and then back to 0.4C. The specific discharge capacity of the lithium-sulfur battery obtained by using the modified diaphragms of Comparative Examples 2-5 decreases by 15-20% from 0.2C through 0.4C, 0.6C, 1C, 2C and then back to 0.4C.
[0108] It can be clearly seen from the above experiments that the transition metal-doped bimetallic MOF-derived heterostructure increases the number of active sites by doping transition metal elements and adjusts the electronic structure of cobalt. The construction of the heterostructure accelerates the transfer of electrons. The synergistic effect between the two-component sulfides enables the electrocatalyst modified membrane to effectively adsorb polysulfides and accelerate the redox reaction kinetics of sulfur.
[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal-doped bimetallic MOF-derived heterostructure, characterized in that The following steps are involved: (1) Co salt, transition metal M salt, dimethyl imidazole and methanol are uniformly mixed, and then allowed to stand to allow metal ions to combine with organic ligands to obtain a bimetallic MOF precursor; (2) dispersing the bimetallic MOF precursor in ethanol to obtain solution 1; dissolving sodium molybdate and thioacetamide in water to obtain solution 2; stirring and mixing solution 1 and solution 2, heating them to perform a solvothermal reaction, and collecting the product after the reaction; (3) The product is calcined under an inert atmosphere to obtain a transition metal-doped bimetallic MOF-derived heterostructure.
2. The heterostructure according to claim 1, characterized in that: In step (1), at least one of the following conditions is included: Condition 1: The transition metal M is selected from Fe, Ni, Zn, Cu or Mn, preferably Zn; Condition 2: The molar amount of Co is 70-90% of the total molar amount of Co and the transition metal M, preferably 90%; Condition 3: The ratio of the sum of the molar amounts of Co and transition metal M to the molar amount of dimethylimidazole is 1: 6-10, preferably 1:8; Condition 4: The total concentration of the Co salt and the transition metal M salt in methanol is 0.01-0.06 mol / L; Condition 5: After mixing the Co salt, the transition metal M salt, dimethylimidazole and methanol, stir at room temperature for 20-40 minutes and then stand at room temperature for 12-24 hours.
3. The heterostructure according to claim 1 or 2, characterized in that: In step (1), the Co salt and transition metal M salt are soluble salts of Co and transition metal M, preferably chlorides or nitrates.
4. The heterostructure according to claim 1, characterized in that: In step (2), the mass ratio of the bimetallic MOF precursor to thioacetamide is 7-10:12; and the molar ratio of sodium molybdate to thioacetamide is 1-3:
8.
5. The heterostructure according to claim 1 or 4, characterized in that: In step (2), during the solvent thermal reaction, the temperature is first raised to 110-140° C. for reaction for 3-5 hours, and then raised to 180-220° C. for reaction for 15-18 hours.
6. The heterostructure according to claim 1, characterized in that: In step (3), the calcination temperature is 320-360° C. and the calcination time is 2-2.5 h.
7. A transition metal-doped bimetallic MOF-derived heterostructure obtained by the method for preparing a transition metal-doped bimetallic MOF-derived heterostructure according to any one of claims 1 to 6.
8. Use of the transition metal-doped bimetallic MOF-derived heterostructure as claimed in claim 7 as a battery separator electrocatalyst.
9. A modified battery separator, characterized in that: It comprises a battery separator body, on which an electrocatalyst layer is coated, wherein the electrocatalyst layer contains the transition metal-doped bimetallic MOF-derived heterostructure as described in claim 7; preferably, the coating thickness of the electrocatalyst layer on the battery separator body is 8-12 μm.
10. Use of the transition metal-doped bimetallic MOF-derived heterostructure according to claim 7 or the modified battery separator according to claim 9 in a lithium-sulfur battery.
Citation Information
Patent Citations
Chalcogenide / graphite carbon cage composite material with short-range ordered structure as well as preparation and application of chalcogenide / graphite carbon cage composite material
CN118929757A
Nail pack
KR1020230166578A
Core-Shell Composites for Shielding Electromagnetic Interference and Method for Preparing the Same
KR102273260B1